Time-Scales of Inter-Eruptive Volcano Uplift Signals: Three Sisters Volcanic Center, Oregon (United States) - Rodríguez-Molina, Sara; González, Pablo J.; Charco, María; Negredo, Ana M.; Schmidt, David A. (Frontiers in Earth Science, 2021)
A classical inflation-eruption-deflation cycle of a volcano is useful to conceptualize the time-evolving deformation of volcanic systems. Such a model predicts accelerated uplift during pre-eruptive periods, followed by subsidence during the co-eruptive stage. However, we lack models to understand low-amplitude persistent deformation, either uplift or subsidence, or even quiescence in the inter-eruptive period when volcanoes appear dormant. Moreover, some volcanoes show puzzling persistent uplift signals with minor or no other geophysical or geochemical variations, which are difficult to interpret. Such temporal behaviors are usually observed in large calderas (e.g, Yellowstone, Long Valley, Campi Flegrei, Rabaul), but less commonly for stratovolcanoes. Therefore, volcano deformation needs to better understood during inter-eruptive stages, to assess its value as a tool for forecasting eruptions. Three Sisters is a complex stratovolcano in Oregon (USA) and offers an example of persistent inter-eruptive uplift signals without associated eruptive activity. Using a Bayesian inversion method, we re-assessed the source characteristics (magmatic system geometry and location) and its uncertainties. Furthermore, we evaluate the most recent evolution of the surface deformation signals combining both GPS and InSAR data through a new non-subjective linear regularization inversion procedure to estimate the 26 year-long volume change time-series. Our results constrain the onset of the Three Sisters volcano inflation to be between October 1998 and August 1999. In the absence of new magmatic inputs, we estimate continuous uplift signal, at diminishing but detectable rates, to last for few decades. Finally, we compare Three Sisters volcano time series with historical uplift at different volcanic systems. Proper modeling of scaled inflation time series indicates a unique and well-defined temporal behaviour. We speculate that common temporal evolution of uplift rates could be a potential indicator of differences in magmatic system dimensions underlying a rather reduced set of the physical processes behind inter-eruptive uplift signals.